KESIAPAN SEKOLAH DASAR BARU MENGHADAPI STANDAR NASIONAL PENDIDIKAN DAN IZIN OPERASIONAL: SEBUAH KAJIAN PERSEKOLAHAN - Imel Sefanya Bako; Deta Maria Sri Darta; Henny Dewi Koeswanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
When a foundation opens a new school, two obligations arrive at once: meeting the National Education Standards (NES) and securing a legally valid operating permit. This study looks closely at that situation at St. Andrew's Primary School Kuatnana, a newly established elementary school under Yayasan Pelita Anglikan Indonesia, a foundation that also runs institutions ranging from a kindergarten to a vocational nursing school. A descriptive qualitative single case study design was used, with data gathered through participatory observation, semi-structured interviews, document review, and literature study, then examined through a gap analysis against the eight NES. Findings show the school still has no valid operating permit, and four facility components a library, a playground, ICT facilities, and instructional aids remain unmet. Readiness across the eight NES is otherwise fairly solid, with five standards judged reasonably ready and three fully ready, so the more pressing obstacles sit in administration and facilities rather than in academic or managerial capacity. The study closes with a phased roadmap for meeting the standards, speeding up the permit process, and moving governance toward more participatory school-based management.